Palmitoylation prevents B7-H4 lysosomal degradation sustaining tumor immune evasion - Yijian Yan; Jiali Yu; Weichao Wang; Ying Xu; Kole Tison; Rongxin Xiao; Sara Grove; Shuang Wei; Linda Vatan; Max Wicha; Ilona Kryczek; Weiping Zou (Nature Communications)
Abstract B7-H4 functions as an immune checkpoint in the tumor microenvironment (TME). However, the post-translational modification (PTM) of B7-H4 and its translational potential in cancer remains incompletely understood. We find that ZDHHC3, a zinc finger DHHC-type palmitoyltransferase, palmitoylates B7-H4 at Cys130 in breast cancer cells, preventing its lysosomal degradation and sustaining B7-H4-mediated immunosuppression. Knockdown of ZDHHC3 in tumors results in robust anti-tumor immunity and reduces tumor progression in murine models. Moreover, abemaciclib, a CDK4/6 inhibitor, primes lysosome activation and promotes lysosomal degradation of B7-H4 independently of the tumor cell cycle. Treatment with abemaciclib results in T cell activation and mitigates B7-H4-mediated immune suppression via inducing B7-H4 degradation in preclinical tumor models. Thus, B7-H4 palmitoylation is an important PTM controlling B7-H4 protein stability and abemaciclib may be repurposed to promote B7-H4 degradation, thereby treating patients with B7-H4 expressing tumors.